Examination of race and gender differences in predictors of neuropsychological decline and development of Alzheimer's disease. Issue 2 (17th February 2022) - Johnson, Ellen E. H.; Alexander, Claire; Lee, Grace J.; Angers, Kaley; Ndiaye, Diarra; Suhr, Julie
Abstract: Objective Black adults are diagnosed with Alzheimer's disease (AD) at higher rates than White adults. Biopsychosocial risk factors that differentially affect individuals by race, including health, education, and APOE e4, may explain these findings. Some research suggests that the risk for AD associated with the APOE e4 allele may differ by race. Gender differences in AD have also been identified but remain understudied. We examined race, APOE status, vascular risk factors, education, and the interaction of APOE e4 status and race as predictors of cognitive decline and the development of Alzheimer's disease between genders in a large longitudinal sample of older adults. Methods: Participants (N = 4336) were selected from the National Alzheimer's Coordinating Center's Uniform Data Set who completed measures of verbal fluency, naming, and immediate/delayed story memory across 5 years. Analyses were stratified by gender. Follow up interactions examined statistical significance of differences. Results: APOE e4 by race interactions were largely non-significant and dropped from most models. When controlling for health, education, referral source, and Uniform Data Set form (when applicable), few racial differences in cognitive performance over time emerged. Black participants obtained lower scores than White participants on a majority of baseline measures. Race findings did not differ by gender. Hypertension was more strongly predictive of decline in delayed memory among women. Conclusions: Analyses did not support that APOE e4 differentially affects Black individuals. Hypertension may be a more relevant risk factor among women. Results raise questions regarding the accuracy of baseline scores in predicting decline for Black individuals.